2012
DOI: 10.1002/j.1681-4835.2012.tb00381.x
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Contextualized Information Systems Curriculum for an Emerging Economy

Abstract: Information Systems (IS) curriculum development in developing countries faces the challenge of balancing conformance to international trends while remaining relevant to the local context. Model curricula such as IS2010 provide a clear and up-to-date reflection of IS curricula trends. However, such curricula cannot be directly implemented especially in developing countries where there are a number of environmental factors that affect the curriculum. In this paper we describe the approach taken to develop a cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…This is important because while the review process, especially for the IS2010 curriculum, has made efforts to be as consultative as possible, the process is still subjective and the final decision on what should be included or excluded lies with the review team. This is supported by observations from other researchers who have pointed out the fact that the curriculum, to a great extent, aligns IS with business faculties which is typical in North American institutions where most of the review body members are based [33,34].…”
Section: Information Systems Curriculumsupporting
confidence: 66%
“…This is important because while the review process, especially for the IS2010 curriculum, has made efforts to be as consultative as possible, the process is still subjective and the final decision on what should be included or excluded lies with the review team. This is supported by observations from other researchers who have pointed out the fact that the curriculum, to a great extent, aligns IS with business faculties which is typical in North American institutions where most of the review body members are based [33,34].…”
Section: Information Systems Curriculumsupporting
confidence: 66%
“…One critical challenge is that that promising engineers cannot always find a proper context for using and developing their skills further. A study in Botswana showed that IT graduates rarely ended up in software development or information systems related jobs, but typical job descriptions were "user support and training", "system administration", and "network administration" [7]. Another study [8] argued that in Africa, in too many cases "graduates leave universities: 1. jobless, 2. without the capacity to find solutions for African problems, 3. pressurized by the family that expects their support, since they have helped them to reach that point, 4. brain draining from rural areas to cities or other countries when the opportunity arises".…”
Section: A Pedagogical Frameworkmentioning
confidence: 99%